Budaya Organisasi Dan Locus Of Control Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Distrik Navigasi Kelas 1 Kota Palembang) - Herlambang, Repandi; Damayanti, Reina; Novalia, Nurkardina (Peneliti.net, 2024)
The purpose of this study was to examine the effect of organizational culture and locus of control on employee performance in the Class 1 Navigation District of Palembang City. This study also examines the mediating role of job satisfaction in the relationship between organizational culture, locus of control, and employee performance in Class 1 Navigation District of Palembang City. The population in this study amounted to 127 employees and the proportional stratified random sampling method was used as the sampling method. This study used a questionnaire for 97 respondents. The analysis technique used is path analysis technique using SPSS version 18.0. The results showed that organizational culture had an effect on job satisfaction in the Class 1 Navigation District of Palembang City, locus of control had no effect on Job Satisfaction in the Class 1 Navigation District of Palembang City. organizational culture has a significant effect on employee performance in the Class 1 Navigation District of Palembang City. And locus of control has a significant effect on employee performance in the Class 1 Navigation District of Palembang City. As well as the variable job satisfaction has a significant effect as a mediation in the relationship between organizational culture and employee performance in the Class 1 Navigation District of Palembang City, while the variable of job satisfaction has no significant effect as a mediation in the relationship between locus of control and employee performance in the Class 1 Navigation District of Palembang City.